COMMITMENT TO LEARNING MEDIATES THE INFLUENCE OF TIME MANAGEMENT AND WELLBEING ON STUDENT LEARNING INDEPENDENCE - Nur Satriani; Sirajuddin Saleh; A. Octamaya Tenri Awaru (SOSIOEDUKASI, 2026)
In facing the demands of higher education in the 21st century digital era, student learning independence is the main key to academic and professional success. Time management and well-being play a crucial role in forming a learning commitment that supports optimal mastery of independence. Therefore, the essence of this study is designed to examine the influence of time management and well-being on student learning independence, with learning commitment as a mediating variable, specifically at the Faculty of Social Sciences and Law (FIS-H) Makassar State University (UNM). This study chose a quantitative approach with the Structural Equation Modeling-Partial Least Square (SEM-PLS) technique analyzed using SmartPLS software. A total of 100 active FIS-H UNM students were selected as respondents through proportionate stratified random sampling from a population of 4,150 students. This study used a Likert scale questionnaire of 1-5 to explore time management, well-being, learning independence and learning commitment, with indicators such as schedule preparation, personal growth, and intrinsic motivation. The research findings are expected to demonstrate a significant influence, both directly and indirectly, between time management and well-being on students' independent learning in the social sciences, with commitment to learning as the primary intermediary. This study concludes that independent learning is key for students in developing independent learning skills and strengthening their academic adaptation.